2022
DOI: 10.3389/fonc.2022.887294
|View full text |Cite
|
Sign up to set email alerts
|

RRM2 Mediates the Anti-Tumor Effect of the Natural Product Pectolinarigenin on Glioblastoma Through Promoting CDK1 Protein Degradation by Increasing Autophagic Flux

Abstract: The natural product pectolinarigenin exerts anti-inflammatory activity and anti-tumor effects, and exhibits different biological functions, particularly in autophagy and cell cycle regulation. However, the antineoplastic effect of pectolinarigenin on glioblastoma (GBM) remains unclear. In the present study, we found that pectolinarigenin inhibits glioblastoma proliferation, increases autophagic flux, and induces cell cycle arrest by inhibiting ribonucleotide reductase subunit M2 (RRM2), which can be reversed b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 43 publications
(48 reference statements)
2
2
0
Order By: Relevance
“…This is in good agreement with the data on the severe delay in colony formation and reduced survival of wild-type yeast under the conditions of 4-NQO action [21,22]. Similarly, in mammals, various modes of transcriptional repression or targeting RRM2 result in the suppression of tumor growth, including GBM [44,59,60]. RNR catalyzes the synthesis of dNTP by a radical mechanism [24], which can be counteracted by the formation of reactive oxygen species.…”
Section: Discussionsupporting
confidence: 89%
“…This is in good agreement with the data on the severe delay in colony formation and reduced survival of wild-type yeast under the conditions of 4-NQO action [21,22]. Similarly, in mammals, various modes of transcriptional repression or targeting RRM2 result in the suppression of tumor growth, including GBM [44,59,60]. RNR catalyzes the synthesis of dNTP by a radical mechanism [24], which can be counteracted by the formation of reactive oxygen species.…”
Section: Discussionsupporting
confidence: 89%
“…Our prognostic model showed low levels of MPC1 expression and high levels of STAT3, RRM2, and TLR4 expression, suggesting a poor prognosis for GBM patients, which was in agreement with previous studies 37–42 . However, our study differed from previous studies in several aspects.…”
Section: Discussionsupporting
confidence: 89%
“… 42 Jiang found that pectolinarigenin promoted autophagic flux through RRM2 suppression, consequently inhibiting the invasion of glioma cells. 43 However, whether tumor antigens can elicit an immune response also depends on the TIME. Due to the high heterogeneity of glioma, only a subset of LGG patients may benefit from mRNA vaccines.…”
Section: Discussionmentioning
confidence: 99%